The Impact of Eco-Friendly Packaging Innovation and Green Branding Communication on Image Green Brand KFC Asia Megamas Medan: Dampak Inovasi Kemasan Ramah Lingkungan dan Komunikasi Green Branding terhadap Citra Merek KFC Asia Megamas Medan - Chandera Rahmatyadi; Hommy Dorthy Ellyany Sinaga (Sekolah Tinggi Ilmu Ekonomi Eka Prasetya, 2025)
This study addresses the challenges arising by increasing environmental concerns and packaging waste in fast food outlets by examining the impact of eco-friendly packaging innovations and green brand communication on the green brand image of KFC Asia Megamas Medan. The aim was to assess the individual effects of green packaging and green brand communication on brand image as well as combined influence. A quantitative approach was used, with incidental sampling techniques to study about 100 KFC consumers, and the data were analyzed with SPSS through validity, reliability, classical assumption tests and multiple linear regression. The results revealed that both eco-friendly packaging innovation and green brand communication had a significant positive effect on green brand image and collectively explained 57.8% of the variance. The results of this study show that integrating eco-friendly packaging innovations with transparent green branding communication can strengthen consumer perception of the image of fastfood brands and direct practical sustainability strategies.